A critical review on energy use and savings in the cement industries - Madlool, N.A.; Saidur, Rahman; Hossain, M.S.; Rahim, N.A. (Elsevier, 2011)
The cement sub-sector consumes approximately 12-15 of total industrial energy use. Therefore, a state of art review on the energy use and savings is necessary to identify energy wastage so that necessary measures could be implemented to reduce energy consumption in this sub-sector. In this paper energy use at different sections of cement industries, specific energy consumption, types of energy use, details of cement manufacturing processes, various energy savings measures were reviewed and presented. Various energy savings measures were critically analyzed considering amount of energy that can be saved along with the implementation cost. Amount of CO(2) reduction has been presented along with the payback period for different energy savings measures as well. This study complied a comprehensive literature on the cement industries in terms of Thesis (MS and PhD), peer reviewed journals papers, conference proceedings, books, reports, websites. It has been observed that China producing major share of global cement production. Coal contribute major share of fuel used in cement industries. However, along with conventional fuels, industries are moving towards the use of alternative fuels to reduce environmental pollution. It was reported that cement industries are moving from wet process to dry process as it consume less energy compared to wet process.